Fe-based layered double hydroxides for removing arsenic from water: sorption-desorption-regeneration - Tuğba Türk; Taha Boyraz; İbrahim Alp (IWA Publishing, 2021)
Since the presence of arsenic in the waters of the world causes serious health effects on people, it is very important to remove it. Layered double hydroxides have a high surface area and high anion exchange capacity, and because of this feature, it is a potential adsorbent to remove arsenic. For regeneration and reuse of adsorbents, researchers in some limited studies have used agents such as acids and alkalis. Media replacement accounts for approximately 80% of the total operational and maintenance costs. In this paper, an adsorption/desorption/regeneration study was carried out with MgFeHT to determine the desorption properties of the adsorbent and to examine its reusability. The best alkaline desorption solution was determined from two different alkaline solutions: NaOH and KH2PO4. As(V) adsorption capacity of the MgFeHT at different pH (3-12) using the arsenic aqueous solution (with 2,000 μg As(V)/L) was evaluated. For the adsorption process, the experimental data are fitted well with the pseudo-second-order kinetic model and the Langmuir model. Moreover, the concentration of 2,000 μg/L arsenic was reduced to below the legal limit determined by the WHO (<10 μg/L). The regeneration studies were conducted on the adsorptive media used in the arsenic removal system. The regeneration efficiency of As(V) was maintained 98.5% for four regeneration cycles using 0.5 M NaOH. MgFeHT was successfully regenerated with an aqueous solution of NaOH and was reused with a small loss of sorption efficiency. HIGHLIGHTS Arsenic toxicity is an important health problem.; Environmental pollution is the biggest problem of industry.; So, economical, easily available, and reusable adsorbent is necessary.; Although several studies have been studied on the desorption of layered double hydroxides with arsenic, almost all studies have focused on arsenic removal capacities.; In this study, it was observed that MgFeHT - as an absorbent - is reusable and economical.;